Identification of a Novel COL4A4 Variant in Compound-Heterozygous State in a Patient With Alport Syndrome and Histological Findings Similar to Focal Segmental Glomerulosclerosis (FSGS) - Zhu, Feng; Li, Wencheng; Li, Zhenqiong; Zhu, Hongyan; Xiong, Jing (Frontiers in Genetics, 2019)
Alport syndrome (AS) is a rare and inherited renal disorder with an autosomal recessive mode of inheritance. AS patients usually manifest with hematuria and progressive renal disorder also occasionally accompanied by hearing loss and ophthalmic disease. Germline variants in collagen type IV α-4 (COL4A4) gene lead to autosomal recessive Alport syndrome. In the present study, we investigated a Chinese family with Alport syndrome. The index patient is a 24-year-old Chinese woman who has been suffering from proteinuria. Renal biopsy and renal pathology were performed and found focal segmental glomerulosclerosis (FSGS) like lesion in the index patient. The index patient also presented with binocular edema and blurred vision. However, binocular edema dissipated gradually without any further treatment. Unlikely, the index patient was not diagnosed with hearing impairment. Index patient’s parents are phenotypically normal. Targeted next generation sequencing and Sanger sequencing was performed. A novel heterozygous single nucleotide insertion, c.4760_4761insC and a previously reported likely pathogenic variant, c.1323_1340delTGGCTTGCCTGGAGCACC in the COL4A4 gene were identified in the index patient. The novel heterozygous single nucleotide insertion (c.4760_4761insC) leads to a frameshift which eventually results in the formations of a truncated COL4A4 protein. In addition, the other heterozygous likely pathogenic variant, c.1323_1340delTGGCTTGCCTGGAGCACC, has been already identified with causing AS an autosomal recessive mode of inheritance. Sanger sequencing confirmed that these two variants were inherited in the index patient from her father and mother, respectively. These two variants were not found in 100 normal control individuals. In conclusion, our present finding emphasizes the significance of high throughput targeted next generation sequencing technology for rapid and cost-effective genetic screening which allows us easy and accurate clinical diagnosis of AS patients.